Privatisasi Air di Indonesia: Saran Pelaksanaan dengan Berkaca dari Pengalaman Negara Lain - Arianti, Vidia (UI Scholars Hub, 2004)
Limited sources of water in the world imposed many countries to give ‘real’ tariffs on water, or in other words, water privatization. Long time ago, water is a public good which people could access freely and cheaply. In the future, there are tendencies that water can no longer be used as public goods, but become private goods, where only certain people who could pay the ‘real’ tariff of water could have access to which. Water privatization has undergone in many countries, as well as in developed, developing, and less developed countries. Besides the limited sources of water, the inability of the government (especially in third world countries) to provide water service for its citizens is getting worse. Governments can no longer give subsidy to its citizens by giving cheap water’s tariff meanwhile the costs to provide clean water is quite high. Governments have limited choice, so privatization becomes the ultimate solution for this problem. Moreover, the World Bank and Asian Development Bank are very keen on these water privatization. The consequence of this water privatization is the significant increase of water tariff. It means that only rich people will have access to clean water while the poor can not pay for the high water tariff. This becomes the central problem of water privatization happened in many countries, for example in South Africa, where 200 people die because of inaccessibility of clean expensive-water. Meanwhile, water privatization in Indonesia that has been legalized through UU No. 7 2004 is underway. Would water privatization become detrimental to Indonesia’s poor people?